Multiturn circulation of an energy-recovery linac beam in a storage ring - T. Nakamura (Physical Review Special Topics. Accelerators and Beams, 2008)
A light source based on the combination of an energy-recovery linac (ERL) and a storage ring is a feasible scheme for next generation light sources. We propose a system with which a beam of an ERL circulates through two or four turns in a storage ring. The system consists of several deflecting cavities and static deflecting magnets. With this system, the average current of the ring can be two or four times higher than that of the ERL, thus easing the burden on the ERL. Resultant low bunch current can lead to a high quality ERL beam and low average current of the ERL can lead to a multipass scheme.